Implementation of Integrative Holistic ECD in Kindergarten South Tangerang City - Leny; susy anggriani; Sukiman; Venty Indah Puspitasi; Siti Maesyaroh; Mulyati (Universitas Panca Sakti Bekasi, 2023)
Holistic-Integrative Early Childhood Development (ECD) is essential, but there are still many Early Childhood Education (ECE) institutions that have not implemented Holistic-Integrative ECD in a comprehensive, integrated and sustainable manner. The purpose of this research is to find out implementation of integrative holistic ECD service in kindergarten South Tangerang City which include education services, health services, nutrition and care services, parenting services, protection services, and child welfare services. This research is expected to be a benchmark for the success of implementing Holistic-Integrative ECD which has been carried out in institutions in South Tangerang City. The research method used is descriptive qualitative. While the data analysis techniques used in this study include: 1) data collection; 2) data reduction, 3) data presentation; and 4) drawing conclusions. The informants for this study were school principals, teachers and parents of students in seven different districts in South Tangerang City. The research was conducted for one month through interviews and distribution of instruments using google forms and documentation. Based on the results of the study it can be concluded that the majority of Kindergartens in South Tangerang City,namely around 89.63% have provided integrative holistic ECD. Out of the five existing services, child welfare services have not been implemented optimally, especially the facilities for making birth certificates and health insurance. This is because the students' parents have carried out the two service components above independently. However, the school will continue to facilitate these services if parents need assistance